Anterior Cruciate Ligament Reconstruction and Radiographic Progression to Knee Osteoarthritis: A Systematic Review - Robbi Tri Atmaja; Arifin; Maya Hapsari Kusumaningtyas (The International Journal of Medical Science and Health Research, 2025)
INTRODUCTION: Anterior cruciate ligament (ACL) injury is a well-established risk factor for the premature development of knee osteoarthritis (OA). ACL reconstruction (ACLR) is the standard of care for restoring knee stability, yet its role in mitigating the long-term radiographic progression of OA remains a subject of intense debate. This review systematically evaluates the evidence on the relationship between ACLR and the long-term development of radiographic knee OA. METHODS: A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library was conducted for studies reporting on radiographic OA outcomes at a minimum 10-year follow-up after ACL injury, with or without reconstruction. Randomized controlled trials (RCTs) and long-term cohort studies were included. Study quality was assessed using the Cochrane Risk of Bias tool for RCTs. Data on OA prevalence, management comparisons (ACLR versus non-operative), surgical variables, and associated risk factors were extracted and synthesized. RESULTS: Seventeen studies involving over 5,000 patients met the inclusion criteria. The prevalence of radiographic knee OA (Kellgren-Lawrence grade ≥2) at a mean follow-up of over 14 years post-ACLR was consistently high, ranging from 20% to over 50%. Comparative analyses between ACLR and non-operative management yielded conflicting results; some evidence suggests ACLR reduces the risk of any degenerative change, while other high-level evidence indicates a higher risk of moderate-to-severe OA in surgically managed cohorts. Concomitant meniscectomy was consistently identified as the most potent predictor of OA progression, with odds ratios ranging from 1.87 to 3.6. No significant differences in tibiofemoral OA rates were found between bone-patellar tendon-bone and hamstring autografts, though graft-specific morbidities were noted. DISCUSSION: The evidence suggests that the initial traumatic event of an ACL injury initiates a degenerative biological cascade that ACLR, a mechanical solution, cannot fully reverse. The procedure's primary benefit is mechanical stabilization, which can prevent secondary meniscal damage. However, its direct chondroprotective effect is often overshadowed by the profound impact of associated meniscal and chondral damage sustained at the time of injury. CONCLUSION: ACLR is effective for restoring knee function but does not eliminate the high long-term risk of radiographic OA. The progression to OA is multifactorial, with the initial injury pattern, particularly meniscal integrity, being a more critical determinant than the surgical intervention itself. Future research should focus on biological interventions to modulate the post-injury inflammatory response.